2012
DOI: 10.7205/milmed-d-11-00388
|View full text |Cite
|
Sign up to set email alerts
|

Financial Well-Being and Postdeployment Adjustment Among Iraq and Afghanistan War Veterans

Abstract: Research has yet to examine the relationship between financial well-being and community reintegration of veterans. To address this, we analyzed data from n=1,388 Iraq and Afghanistan War Era Veterans who completed a national survey on post-deployment adjustment. The results indicated that probable major depressive disorder, posttraumatic stress disorder, and traumatic brain injury were associated with financial difficulties. However, regardless of diagnosis, veterans who reported having money to cover basic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 40 publications
3
73
1
Order By: Relevance
“…[4][5][6]. Strict weapons' prohibition law in addition may decline fatalities as well, during personal rivalries and family quarrels [2,12,20]. The Open Access Journal of Science and Technology…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]. Strict weapons' prohibition law in addition may decline fatalities as well, during personal rivalries and family quarrels [2,12,20]. The Open Access Journal of Science and Technology…”
Section: Discussionmentioning
confidence: 99%
“…These are shown in appendix I. Elbogen, Johnson, Wagner, Newton, and Beckham (2012) found that military veterans post-deployment with mental health problems or brain injury were more likely to have large unsecured debts, whilst…”
Section: Other Studiesmentioning
confidence: 99%
“…In addition, poor employment outcomes result in serious financial issues, including low income (Zivin et al, 2011) and difficulties meeting basic life needs, such as food and shelter (Elbogen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%